2015
DOI: 10.2310/8000.2013.131285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pain control in suspected acute appendicitis on the diagnostic accuracy of surgical residents

Abstract: Objective: To determine the influence of early pain relief for patients with suspected appendicitis on the diagnostic performance of surgical residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…For children and adolescents, tailoring the history and physical examination to their age and developmental level is essential, and the examiner's experience plays a vital role, especially with younger children. Administering analgesics does not significantly obscure clinical findings [41]. In pediatric cases, the absence of symptoms such as nausea, vomiting, abdominal tenderness, and leukocytosis effectively rules out appendicitis with a 98% accuracy [42].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…For children and adolescents, tailoring the history and physical examination to their age and developmental level is essential, and the examiner's experience plays a vital role, especially with younger children. Administering analgesics does not significantly obscure clinical findings [41]. In pediatric cases, the absence of symptoms such as nausea, vomiting, abdominal tenderness, and leukocytosis effectively rules out appendicitis with a 98% accuracy [42].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…La presencia de este fenómeno ha sido evidenciada en diferentes estudios, además de ser un argumento asociado a la evolución clínica. [14][15][16][17] En nuestro país, la escala RIPASA ha reportado una sensibilidad de 93.3% con una especificidad de 8.3%, un valor predictivo positivo de 91.8% y un valor predictivo negativo de 10.1%. 18 Ninguna de las series de evaluación diagnóstica y validación de esta prueba ha reportado el consumo de AINE dentro de sus subgrupos de análisis.…”
Section: Introductionunclassified
“…2,3 However, this belief has been clearly refuted by recent evidence. 1,[4][5][6][7] Multiple pediatric randomized controlled trials and a recent systematic review demonstrated that, when opioid analgesia is provided, there is no difference in accuracy and timeliness of diagnosis of appendicitis and no difference in rates of appendicitis-related complications. 1,5,6,8 Further, a Cochrane review of adults with acute abdominal pain has also demonstrated that analgesia does not mask appendicitis or delay the diagnosis.…”
Section: Introductionmentioning
confidence: 99%